2020
DOI: 10.3390/nu12051408
|View full text |Cite
|
Sign up to set email alerts
|

Eating Habits Associated with Nutrition-Related Knowledge among University Students Enrolled in Academic Programs Related to Nutrition and Culinary Arts in Puerto Rico

Abstract: University students frequently develop unhealthy eating habits. However, it is unknown if students enrolled in academic programs related to nutrition and culinary arts have healthier eating habits. We evaluated the relationship of eating habits and nutritional status of students in academic programs with knowledge on nutrition, as well as cooking methods and techniques. A descriptive cross-sectional study was conducted in spring of 2019, while we completed a survey measuring eating habits and knowledge on nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 28 publications
4
20
0
6
Order By: Relevance
“…This can be attributed to the effect of knowledge on changing dietary practices, with the outcome of a normal BMI. This finding is similar to a previous study [18] which reported a relationship between normal BMI and nutrition academic programs. On the other hand, another study [42] documented that there was no relationship between a normal BMI and the practice of healthy eating habits.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This can be attributed to the effect of knowledge on changing dietary practices, with the outcome of a normal BMI. This finding is similar to a previous study [18] which reported a relationship between normal BMI and nutrition academic programs. On the other hand, another study [42] documented that there was no relationship between a normal BMI and the practice of healthy eating habits.…”
Section: Discussionsupporting
confidence: 92%
“…However, the transition from school to college life gives more freedom in the type and the amount of food consumption. Some studies related to awareness of a healthy diet have proven that students have a fair knowledge of nutritional requirements for health [18,[28][29][30][31]. In our study, 71.6% of the students were enrolled in a nutrition course, and 84.9% understood the concept of a healthy diet.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…“Eating habits” can be defined as the conscious and repetitive way a person eats, and this includes what types of food are eaten, their quantities and timing of consumption, in response to cultural and social influences [ 9 ]. On the other hand, “eating behaviors” have been considered as a group of actions starting from a simple food chewing to food shopping, food preparation and food policy decision-making [ 10 ].…”
Section: Definitionsmentioning
confidence: 99%
“…However, some researches have not noted such associations [25]. Rivera Medina et al found that dietary habits were associated with nutritional knowledge but not with knowledge on cooking methods and techniques [26].…”
Section: Introductionmentioning
confidence: 99%